2017
DOI: 10.1002/ase.1685
|View full text |Cite
|
Sign up to set email alerts
|

Climbing Bloom's taxonomy pyramid: Lessons from a graduate histology course

Abstract: Bloom's taxonomy was adopted to create a subject-specific scoring tool for histology multiple-choice questions (MCQs). This Bloom's Taxonomy Histology Tool (BTHT) was used to analyze teacher- and student-generated quiz and examination questions from a graduate level histology course. Multiple-choice questions using histological images were generally assigned a higher BTHT level than simple text questions. The type of microscopy technique (light or electron microscopy) used for these image-based questions did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 50 publications
0
46
0
1
Order By: Relevance
“…However, few studies have looked into the effect of the flipped classroom on critical thinking by exploring students ability to answer higher‐level analytical examination questions (Day, ; Morton and Colbert‐Getz, ). Bloom's revised taxonomy (Anderson et al, ) can be utilized as informative tool to assess the level of knowledge required to answer multiple choice questions (Thompson and O'Loughlin, ; Zaidi et al, ). This level of analysis can help measure the effectiveness of an assessment in light of critical thinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have looked into the effect of the flipped classroom on critical thinking by exploring students ability to answer higher‐level analytical examination questions (Day, ; Morton and Colbert‐Getz, ). Bloom's revised taxonomy (Anderson et al, ) can be utilized as informative tool to assess the level of knowledge required to answer multiple choice questions (Thompson and O'Loughlin, ; Zaidi et al, ). This level of analysis can help measure the effectiveness of an assessment in light of critical thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple‐choice questions (MCQ) are frequently used in anatomical and foundational courses as a mode of assessment, but further analysis of questions based on Bloom's can be extremely informative of the level of cognition obtained by a student (Haak et al, , Thompson and O'Loughlin, ). Although Bloom's was originally designed to be a general non‐discipline specific resource, several discipline specific tools have been developed to assist educators with determining the Bloom's level of MCQs, including “Bloom's Anatomy Tool” (BAT) (Thompson and O'Loughlin, ), “Bloom's Taxonomy Histology Tool” (Zaidi et al, ), and “Blooming Biology Tool” (Crowe et al, ). These tools have allowed for a measurable interrater reliability when assessing the effects of changes in classroom education through the students' performance on MCQ examinations.…”
Section: Introductionmentioning
confidence: 99%
“…We should remember that the elaboration of educational objectives of the course was based on the Bloom's Taxonomy (cognitive, affective and psychomotor). Other researches also used this reference in the elaboration of assessment activities, courses and disciplines with the purpose of assessing cognitive gain in higher levels of learning (20)(21)(22) .…”
Section: -Cardiac Rhythms Of Cardiopulmonary Arrest and Automatedmentioning
confidence: 99%
“…Based on the thinking of many researchers about the cumulative hierarchy (Cizek et al, ; Dobson, ; Knecht, ; Harries and Botha, ; Crowe et al, ; Kim et al, ; Thompson and O'Loughlin, ; Choudhury et al, ; Semsar and Casagrand, ; Zaidi et al, ), it was expected that student performance at knowledge and comprehension levels, either individually or on both levels, would be greater than student performances at application and/or analysis levels. This hypothesis provides sufficient flexibility without demanding that the trend in scores be strictly hierarchical (i.e., knowledge would be higher than comprehension, which would be higher than application, which would be higher than analysis).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the BAT did not improve accuracy or inter‐rater reliability but was easy to use. Expanding on the BAT, Zaidi et al () developed the Bloom's Taxonomy Histology Tool (BTHT) for student use to develop both a deeper level of content mastery and critical thinking. These studies and others like them involve the assumption that Bloom's taxonomy is multi‐tiered along a continuum of simple to complex (Cizek et al, ; Kim et al, ; Semsar and Casagrand, ).…”
Section: Introductionmentioning
confidence: 99%